An infrared filter radiometer for atmospheric cluster-ion detection. - Aplin, K; McPheat, R (2008)
Motivated by the detection of infrared absorption bands from atmospheric cluster ions in laboratory experiments, a narrowband filter radiometer has been constructed for ion detection in the atmosphere. It uses a filter centered at 9.15 mum wavelength with 5% bandwidth, protected by a diamond-like-carbon coated germanium auxiliary filter, and fitted to a standard pyrradiometer. A sensitivity of (29.3+/-0.1) microV/(W m(-2)) has been determined in a laboratory calibration using a blackbody source. Atmospheric experiments show that the filter radiometer, when used with a stable, low-noise amplifier, can respond to cluster-ion fluctuations. The filter radiometer's sensitivity to atmospheric ion changes is (0.47+/-0.05) (mW m(-2))/(ions cm(-3)).